2001
DOI: 10.1007/s11661-001-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Interface heat transfer in investment casting of aluminum alloys

Abstract: Via design of experiments and using a newly developed inverse method, the heat-transfer boundary conditions in the investment casting process have been studied. It has been shown in the past that these conditions, expressed as interface heat transfer coefficients (HTCs), vary during alloy solidification and cooling. In this work, the authors have studied the additional effects of alloy solidification range, metallostatic head, investment shell thickness, preheat, and interface geometry. This provides an improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…(2) Most studies presented in the literature assume the presence of quasi-steady state conditions at the interface, 8,11) i.e. the heat flux flowing out of the metal is equal to that which flows into the mold.…”
Section: Effective Heat Transfer Coefficient Hmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Most studies presented in the literature assume the presence of quasi-steady state conditions at the interface, 8,11) i.e. the heat flux flowing out of the metal is equal to that which flows into the mold.…”
Section: Effective Heat Transfer Coefficient Hmentioning
confidence: 99%
“…Hwang et al 10) conducted a similar investigation using an A356 aluminum alloy casting in a sand mold. Utilizing an inverse technique, Browne and O'Mahoney 11) showed that the interfacial thermal resistance in an investment casting process was related to the solidification range of the alloy, the hydrostatic pressure of the liquid metal, the thickness of the investment shell, the pre-heat conditions, and the interface geometry. Chiesa 12) measured the temperature of the molten metal during the filling of a flat plate mold, and concluded that the difference between the measured temperature value and the numerically-derived temperature value implied the presence of a thermal resistance at the mold/ metal interface even though the metal was in a molten state.…”
Section: Introductionmentioning
confidence: 99%
“…As the cooling of the ingot progresses, an unusual experimental behavior is noticed. This could be interpreted in terms of the variation of the heat transfer coefficient between the metal and the mold, just as it has been suggested by authors such as GRIFITH [3], BROWNE and O'MAHONEY [4], and TAHA et al [5]. Figure 6 represents the experimental and theoretical cooling curves for the case in which the alloy was cast in a mold at 300°C.…”
Section: Resultsmentioning
confidence: 69%
“…Controlling both stages is of major importance for obtaining sound casts with the required geometry and mechanical properties as observed by (Kobryn and Semiatin, (2000), Browne and O'Mahoney, (2001) and Martorano and Capocchi, (2000). When molten metal is poured into the mould cavity, it is initially in the liquid state with a high fluidity.…”
Section: Numerical Simulations Of Differential Equationsmentioning
confidence: 99%